Job satisfaction based on gender and years of experience among teachers of English language in Iran - Tehrani, Hesam Tahsildar; Hassan, Siti Aishah (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
The aim of the current study is to examine the possible role of English teachers‟ Experience (regardless of their gender) in job satisfaction. Respondents included 98 teachers Of English in Iranian Language Schools. A Likert-type questionnaire was distributed online among Iranian EFL language teachers. The main purpose was to examine if the independent variables (gender and years of experience) can significantly explain the variation of job satisfaction. The findings indicate that only years of teaching variable explained most of the increment of job satisfaction (βi = -0.334, p < .05) However, gender did not influence job satisfaction (βi = -0.88, p > .05).